2017
DOI: 10.1016/j.heliyon.2017.e00420
|View full text |Cite
|
Sign up to set email alerts
|

Titanium addition influences antibacterial activity of bioactive glass coatings on metallic implants

Abstract: In an attempt to combat the possibility of bacterial infection and insufficient bone growth around metallic, surgical implants, bioactive glasses may be employed as coatings. In this work, silica-based and borate-based glass series were synthesized for this purpose and subsequently characterized in terms of antibacterial behavior, solubility and cytotoxicity. Borate-based glasses were found to exhibit significantly superior antibacterial properties and increased solubility compared to their silica-based counte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 55 publications
0
24
0
Order By: Relevance
“…Furthermore, fluoride ion application to a wound dressing remarkably reduces bacterial growth and promotes cell proliferation 16) . In addition, bioactive glass including borate is more resistant to Escherichia coli than silica-based glass 17) . Antibacterial effects of fluoride and borate were reported to promote wound healing as a secondary effect 18,19) .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, fluoride ion application to a wound dressing remarkably reduces bacterial growth and promotes cell proliferation 16) . In addition, bioactive glass including borate is more resistant to Escherichia coli than silica-based glass 17) . Antibacterial effects of fluoride and borate were reported to promote wound healing as a secondary effect 18,19) .…”
Section: Introductionmentioning
confidence: 99%
“…No significant differences were detected for the 13-93 and 13-93-B3 coatings, while the The effect of the 13-93 and 13-93-B3 BG coated Ti on various microorganisms (E. faecalis, E. coli, P. aeruginosa, S. aureus) was evaluated after incubation at 37 °C for 24 h. The results of the OD600 nm measured with a BioPhotometer are shown in Figure 7, where the OD values are properly multiplied for the dilution factor. It is possible to note that even if borate glasses should have antibacterial properties, as follows from the literature [28][29][30], all microbiology tests show a rather high Figure 6. Optical microscopic images taken after staining with Alizarin Red S of ADMSCs cultured in the presence of (a,b) 13-93 BG coated Ti, (c,d) 13-93-B3 BG coated Ti in osteogenic medium, (e,f) positive control and (g,h) negative control (ADMSCs cultured with or without osteogenic medium, respectively) for three weeks.…”
Section: Biological Propertiesmentioning
confidence: 71%
“…To obtain crystalline films, nanosecond PLD deposition is usually performed by the heating of the substrate or by using a buffer gas [41,44,45], so we can expect that also the deposited films are amorphous. We deposited the films at room temperature since it was demonstrated that amorphous materials show superior solubility in biological or simulated biological fluid media and are characterized by an increased bioactivity with respect to crystalline materials [8,9,29,46].…”
Section: Physico-chemical Characterizationmentioning
confidence: 99%
See 2 more Smart Citations